EVOLUTION OF DIAGNOSTIC TECHNIQUES OF DEATH: AYURVEDA PERSPECTIVE AND MODERN TRENDS IN INDIA - Kamal, Gopendra Chandra; Ballav, Sourav; Bharati, Ashwini Kumar S (International Journal of Research -GRANTHAALAYAH, 2018)
Background: Death is the permanent and irreversible cessation of the tripod of life, viz. the brain, the heart and the lungs. However, there exist philosophical, religious and cultural differences in the concept of death. The diagnosis of death has medical and legal implications which have come a long way over the years and in the regions. Method: The references available regarding the diagnostic techniques for declaring death in classical text were studied and compared with the available information in the contemporary medical literatures and published articles. Result: A number of Ayurveda literatures such as Charaka Samhita, Sushruta Samhita, Astangahrdayam, Vishavaidyasarasamuchhaya, Vishavaidya jyotsnika etc. written in different era by authors from different region have put forward their techniques for diagnosing death which are mostly similar, simple and gross. With the advent of technology and the development of Modern medical sciences, the clincians in India have been following the western system mostly the one practiced in United Kingdom for diagnosing death. The focus has shifted the cardio-respiratory cessation to brain-stem death due to the development of artificial ventilator system and scope for organ transplantation. However, there is need for universal guidelines and much progress have been made regarding the same. Some of the governing laws in this regard in India are Transplantation of Organ Act (THO Act 1994, 2011, 2014) and THO Rules 1995. Conclusion: Ayurveda criteria also focused on declaring death based on the cessation of the function of the three vital organs, although using different sets of techniques. Better, more specific and accurate techniques have evolved over the years.